Improving bitumen detection in resistivity surveys by using induced polarisation data. Issue 5 (1st October 2018) - Mashhadi, Seyyed Reza; Mostafaei, Kamran; Ramazi, Hamidreza
Abstract : This paper investigates the use of induced polarisation (IP) and resistivity methods to characterise bitumen deposits in western Iran. Specifically we explore the Barreh-palang bitumen deposit in Gilan-gharb, Kermanshah province, Iran. These deposits are mainly found in vertical structures and, in some cases, complicated fault and fracture structures. Additionally, the hydrogeophysical environment adds complexity due to elevated groundwater levels that are of moderate to high salinity. Both resistivity and IP data were recorded using a combined resistivity sounding and profiling (CRSP) array with potential electrode spacing of 5 m in four profiles. Several anomalous responses were detected. For several of these responses, the bitumen-rich zone was difficult to distinguish from other responses without the IP data, implying that resistivity alone is not always sufficient for detection of bitumen, especially in complex geological situations. Interestingly, we also show that the presence of saline water was useful to assist in detecting the target in some situations. Abstract : A hydrogeophysically and geologically complex bitumen deposit in western Iran was investigated by means of resistivity and induced polarisation (IP) methods. The results show the high potential of IP data to improve bitumen detection. It was also proven that saline water can sometimes be useful in target identification in mineral explorations.